Local configurations in ErBa2Cu3O6+x for 0.15≤x≤0.9 - Varotto, M; Amoretti, G; Bucci, C; De Renzi, R; Guidi, G; Jang, S; Radaelli, P; Segre, C (1994)
The NQR spectra of Cu in several ErBa2Cu3O6+x powder samples (0.1≤x≤0.9), characterized by particularly careful annealing, shows a limited number of frequency peaks. This fact is taken as evidence of a high degree of ordering of O(4) in the chain Cu(1) layer of the perovskite (formation of long full chains separated by empty chains as dictated by the stoichiometry), leading to a few regular patterns in the local configurations. © 1994.